Impact of deltamethrin-resistance in Aedes albopictus on its fitness cost and vector competence. - Jielin Deng; Yijia Guo; Xinghua Su; Shuang Liu; Wenqiang Yang; Yang Wu; Kun Wu; Guiyun Yan; Xiao-Guang Chen (Public Library of Science (PLoS), 2021)
Background Aedes albopictus is one of the most invasive species in the world as well as the important vector for mosquito-borne diseases such as dengue fever, chikungunya fever and zika virus disease. Chemical control of mosquitoes is an effective method to control mosquito-borne diseases, however, the wide and improper application of insecticides for vector control has led to serious resistance problems. At present, there have been many reports on the resistance to pyrethroid insecticides in vector mosquitoes including deltamethrin to Aedes albopictus. However, the fitness cost and vector competence of deltamethrin resistant Aedes albopictus remain unknown. To understand the impact of insecticide resistant mosquito is of great significance for the prevention and control mosquitoes and mosquito-borne diseases. Methodology/principal findings A laboratory resistant strain (Lab-R) of Aedes albopictus was established by deltamethrin insecticide selecting from the laboratory susceptible strain (Lab-S). The life table between the two strains were comparatively analyzed. The average development time of Lab-R and Lab-S in larvae was 9.7 days and 8.2 days (P < 0.005), and in pupae was 2.0 days and 1.8 days respectively (P > 0.05), indicating that deltamethrin resistance prolongs the larval development time of resistant mosquitoes. The average survival time of resistant adults was significantly shorter than that of susceptible adults, while the body weight of resistant female adults was significantly higher than that of the susceptible females. We also compared the vector competence for dengue virus type-2 (DENV-2) between the two strains via RT-qPCR. Considering the results of infection rate (IR) and virus load, there was no difference between the two strains during the early period of infection (4, 7, 10 day post infection (dpi)). However, in the later period of infection (14 dpi), IR and virus load in heads, salivary glands and ovaries of the resistant mosquitoes were significantly lower than those of the susceptible strain (IR of heads, salivary glands and ovaries: P < 0.05; virus load in heads and salivary glands: P < 0.05; virus load in ovaries: P < 0.001). And then, fourteen days after the DENV-2-infectious blood meal, females of the susceptible and resistant strains were allow to bite 5-day-old suckling mice. Both stains of mosquito can transmit DENV-2 to mice, but the onset of viremia was later in the mice biting by resistant group as well as lower virus copies in serum and brains, suggesting that the horizontal transmission of the resistant strain is lower than the susceptible strain. Meanwhile, we also detected IR of egg pools of the two strains on 14 dpi and found that the resistant strain were less capable of vertical transmission than susceptible mosquitoes. In addition, the average survival time of the resistant females infected with DENV-2 was 16 days, which was the shortest among the four groups of female mosquitoes, suggesting that deltamethrin resistance would shorten the life span of female Aedes albopictus infected with DENV-2. Conclusions/significance As Aedes albopictus developing high resistance to deltamethrin, the resistance prolonged the growth and development of larvae, shorten the life span of adults, as well as reduced the vector competence of resistant Aedes albopictus for DENV-2. It can be concluded that the resistance to deltamethrin in Aedes albopictus is a double-edged sword, which not only endow the mosquito survive under the pressure of insecticide, but also increase the fitness cost and decrease its vector competence. However, Aedes albopictus resistant to deltamethrin can still complete the external incubation period and transmit dengue virus, which remains a potential vector for dengue virus transmission and becomes a threat to public health. Therefore, we should pay high attention for the problem of insecticide resistance so that to better prevent and control mosquito-borne diseases.